Piezoelectric properties of (1 - x)Pb(Zr1/2Ti1/2)O3-xPb(Zn1/3Nb2/3)O3 ceramics prepared by the columbite-(wolframite) precursor method - Vittayakorn, N.; Puchmark, C.; Rujijanagul, G.; Tan, X.; Cann, D. P. (My University, 2006)
Solid solutions of the perovskite structure, (1 - x)Pb(Zr1/2Ti1/2)O3-xPb(Zn1/3Nb2/3)O3 with x = 0.1-0.5, were synthesized via the columbite-(wolframite) precursor method. The phase development of calcined powder precursors was analyzed by X-ray diffraction. Phase-pure perovskite of PZN-PZT ceramics was obtained over a wide compositional range. The microstructure and piezoelectric properties were characterrized by means of scanning electron microscopy (SEM), d33 measurements and impedance analysis. It has been found that ultra-high piezoelectric properties were observed in compositions close to a morphotropic phase boundary (MPB). The maximum value of d33 (690 pC/N) and the highest kp (0.7) were recorded for the composition x = 0.3 located at the boundary between tetragonal and rhombohedral ferroelectric phases. Furthermore, large values of d33 (600 pC/N) and kp (0.67) were observed at a compositions of x = 0.5, which is the boundary between two ferroelectric rhombohedral phases. © 2005 Elsevier B.V. All rights reserved.
Keywords: Ferroelectricity; Phase transitions; Piezoelectricity; PZT